2014
DOI: 10.1158/1541-7786.mcr-13-0673
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interactions between Cancer Cells and the Embryonic Microenvironment Regulate Cell Invasion and Reveal EphB6 as a Metastasis Suppressor

Abstract: Metastatic dissemination drives the high mortality associated with melanoma. However, limitations in visualizing in vivo cell dynamics during metastatic invasion have limited our understanding of these cell behaviors. Recent evidence has revealed that melanoma cells exploit portions of their ancestral embryonic neural crest emigration program to facilitate invasion. What remains to be determined is how embryonic microenvironmental signals influence invasive melanoma cell behavior, and whether these signals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
5
28
0
Order By: Relevance
“…Collectively, these results demonstrate for the first time a role for EPHB6 in the metastatic spread of colorectal tumors. Although these findings await further validation using additional experimental approaches, the effects of EPHB6 modulation on the metastatic potential of colon cancer cells are consistent with the role of this EPH receptor in the metastatic progression of other tumor types, such as melanoma, breast and lung tumors111325262733.…”
Section: Discussionsupporting
confidence: 60%
“…Collectively, these results demonstrate for the first time a role for EPHB6 in the metastatic spread of colorectal tumors. Although these findings await further validation using additional experimental approaches, the effects of EPHB6 modulation on the metastatic potential of colon cancer cells are consistent with the role of this EPH receptor in the metastatic progression of other tumor types, such as melanoma, breast and lung tumors111325262733.…”
Section: Discussionsupporting
confidence: 60%
“…EPHB6 lacks catalytic activity due to several intrinsic alterations in the sequence of its kinase domain [4] and in contrast to other Eph receptors [57], EPHB6 is often downregulated in various malignancies, including metastatic lung cancer [8], melanoma [9], prostate cancer [10], ovarian carcinoma [11], gastric cancer [12], aggressive neuroblastoma [13, 14], and invasive breast cancer cell lines [15, 16]. This agrees well with the previously reported EPHB6 ability to suppress metastasis in non-small cell lung cancer [17] and melanoma [18], and our own findings that EPHB6 actively reduces breast cancer invasiveness [19]. Taken together, these observations indicate that EPHB6 receptor deficiency may potentially be targeted by using the SL approach to further personalize cancer therapy and improve treatment in multiple malignancies.…”
Section: Introductionsupporting
confidence: 89%
“…EphB6-expressing melanoma cells displayed significantly reduced metastatic potential in a chorioallantoic membrane metastasis assay. The authors identified EphB6 as a metastasis suppressor in melanoma, probably acting at the stage of intravasation 22. Anoikis is a specific type of apoptosis induced by detachment of epithelial cells from the extracellular matrix, and acquiring resistance to anoikis is an important step that enables cancer cells to metastasise.…”
Section: Discussionmentioning
confidence: 99%